Sosialisasi SADARI sebagai strategi efektif membangun ketahanan kesehatan reproduksi - Holida, Siti Solihat; Yusdian, Yudi (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Pest control with pesticides effectively increases agricultural yields, but exposure to synthetic compounds such as organophosphates carries the risk of neurological damage, reproductive disorders, and carcinogenesis, including increased incidence of breast cancer. Students from the Faculty of Agriculture, Bale University, Bandung, are vulnerable to exposure during field practice, while their knowledge of early breast cancer detection remains low. The Breast Self-Examination (SADARI) education program is proposed as a low-cost and practical preventive measure to increase awareness and early detection skills. This initiative supports students' role as agents of change in strengthening the health of rural communities. Purpose: To increase knowledge and awareness among students from the Faculty of Agriculture, Bale University, Bandung, regarding reproductive health and SADARI as an early detection method for breast cancer. Method: The type of activity carried out was health education to the community with the theme